Stabilized Sulfonated Aromatic Polymers by in situ Solvothermal Cross-Linking - Di Vona, Maria Luisa; Sgreccia, Emanuela; Narducci, Riccardo; Pasquini, Luca; Hou, Hongying; Knauth, Philippe (Frontiers in Energy Research, 2014)
The cross-link reaction via sulfone bridges of sulfonated polyetheretherketone (SPEEK) by thermal treatment at 180 °C in presence of dimethylsulfoxide (DMSO) is discussed. The modifications of properties subsequent to the cross-linking are presented. The mechanical strength as well as the hydrolytic stability increased with the thermal treatment time, i.e., with the degree of cross-linking. The proton conductivity was determined as function of temperature, IEC, degree of cross-linking and hydration number. The memory effect, which is the membrane ability to “remember” the water uptake reached at high temperature also at lower temperature, is exploited in order to achieve high values of conductivity. Membranes swelled at 110 °C can reach a conductivity of 0.14 S/cm at 80°C with a hydration number () of 73.